Therapeutic efficacy of TMTP1-modified EVs in overcoming bone metastasis and immune resistance in PIK3CA mutant NSCLC - Liwen Liu; Tanghesi Wuyun; Xin Sun; Yu Zhang; Geqi Cha; Ling Zhao (Cell Death and Disease)
Abstract Non-small cell lung cancer (NSCLC) with PIK3CA mutations demonstrates significant challenges in treatment due to enhanced bone metastasis and immune checkpoint resistance. This study investigates the efficacy of tumor-targeting peptide 1-modified cancer stem cell-derived extracellular vesicles (TMTP1-TSRP-EVs) in reshaping the tumor microenvironment and reversing immune checkpoint resistance in NSCLC. By integrating TMTP1-TSRP into EVs, we aim to specifically deliver therapeutic agents to NSCLC cells, focusing on inhibiting the PI3K/Akt/mTOR pathway, a crucial driver of oncogenic activity and immune evasion in PIK3CA-mutated cells. Our comprehensive in vitro and in vivo analyses show that TMTP1-TSRP-EVs significantly inhibit tumor growth, reduce PD-L1 expression, and enhance CD8+ T cell infiltration, effectively reversing the immune-suppressive microenvironment. Moreover, the in vivo models confirm that our approach not only suppresses bone metastases but also overcomes primary resistance to immune checkpoint inhibitors by modulating the expression of key immunological markers. These findings suggest that targeted delivery of TMTP1-TSRP-EVs could provide a novel therapeutic strategy for treating PIK3CA-mutant NSCLC, offering significant improvements over traditional therapies by directly targeting the molecular pathogenesis of tumor resistance and metastasis. Molecular Mechanisms Reshaping the TME to Halt PI3K-Mutant Bone Metastasis of NSCLC and Overcoming Primary ICI Resistance. (Created by BioRender).